KAJIAN PELATIHAN KURIKULUM 2013 OLEH INSTRUKTUR KABUPATEN/KOTA KEPADA GURU SEKOLAH SASARAN - Etty Sisdiana (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2019)
This study aims to produce recommendations that can be proposed as policy materials for the K-2013 training that can precisely support its implementation. The study used qualitative methods with data analysis written descriptively. Data collection was carried out in locations that were carrying out K-2013 training in 2016, including: Bandung, Yogyakarta, Badung, Makassar, Tidore and Sorong District. Data collection was carried out using interview, observation, and FGD techniques, with data sources including: LPMP leaders, heads of district / city education offices, resources teachers, regency instructor (IK), and training facilities. The findings of the study are: 1) District / City Education Quality Evaluation Institution (LPMP) and education office have not been able to play an optimal role in K-2013 training, 2) Unqualified IK are still found even though selection and training process has been passed by candidates, 3) the majority of training room conditions are less comfortable and facilities such as student textbooks are still inadequate for training needs, 4) there are materials that are not in accordance with the needs of the teacher to carry out learning, 5) the amount of training time is not enough. Recommendations for reorientation of training include: 1) the role of LPMP and district / city education office, 2) IK recruitment system, 3) fulfillment of facilities and infrastructure according to training needs, 4) arranging schedules and time requirements for training material presentation, 5) setting priority materials. Keywords: Curriculum 2013, Training, Instrument and Infrastructure